Культурні особливості історико-етнографічних регіонів України - Кіреєва, С. О. (ХНУРЕ, 2022)
In different historical periods on the territory of Ukraine historical and ethnographic regions were formed. They are characterized by different sizes, individual characteristics of history, economic specialization, ethnic composition and traditions of the population, original material and spiritual culture. In this article considers and describes the processes of formation of historical-ethnographic regions of Ukraine and their features.